Ethnic Discrimination, Coping Strategies, and Psychological Well-Being Among Indigenous Communities in San Gabriel, LA Union: A Correlational Study - Ana Fei Aliten Arellano; Andrew S. Macalma (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2026)
The study explored the link between ethnic discrimination and psychological well-being among Indigenous people in San Gabriel, La Union, focusing on the coping strategies they use. Perceived Discrimination Scale, Discrimination Coping Strategies Scale, and Ryff's Psychological Well-Being Scale were among the modified standardized questionnaires used to gather data from 200 Indigenous participants using a descriptive-correlational approach. The results showed that respondents commonly encountered moderate degrees of ethnic prejudice, especially stereotypes pertaining to cultural identity and place of origin. There is a significant negative association (p = -0.644, p < 0.001) between psychological well-being and ethnic discrimination. This suggests that as discriminatory experiences increase, levels of well-being decrease. Despite all these challenges, participants reported frequently employing adaptive coping methods in reaction to discrimination, such as seeking social support, clearing misconceptions, and retaining ethnic pride. Retaliatory coping and avoidance were less frequently reported. To address discrimination and strengthen psychological well-being, the findings underscore the tenacity of Indigenous communities and the necessity of culturally appropriate therapies, peer-support programs, and legislative measures.